International Accounting Practices . - Kollaritsch, Felix P. (The Accounting Review, 1965)
In this article, the author analyzes some of the unique accounting practices in foreign countries. A study of international accounting practices reveals an array of methods and procedures. Some nations still use the primitive accounting techniques which most industrialized nations considered outmoded fifty years ago; on the other hand, a number of nations now employ the most advanced accounting methods, supported by up-to-date laws. International accounting is important because it gives us the opportunity to study historical accounting methods supported. More than that, however, one can learn from the failures and successes of nations that have applied accounting methods different from ours to solve many of the same problems now facing people. The relative merits of flexibility as compared with uniformity of accounting principles, procedures and methods have been under much discussion in the United States. Although there is no space here for detailed investigation, it is interesting to note that there are still three nations in which complete or partial uniformity was or is still required by law.